Citizenship in Britain : a history - Heater, Derek Benjamin (Edinburgh University Press, 2006)
An historical introduction to the varieties of citizenship in Britain, starting in the Middle Ages and bringing the story right up to the present day. Both the status and understanding of citizenship in practice and the theoretical and advisory writings on the subject are introduced, and their inter-relationships are explored. Among the key themes to be examined are: local and national strata the issue of parliamentary suffrage women excluded and included as citizens the influence of classical ideas nationhood and imperialism the role of political and social theorists interpretations by modern political parties the role of education environmental citizenship multiculturalism globalisation human rights Organised chronologically, each chapter is divided into sections in order to present the reader with different themes in a manageable form. The focus throughout is on accessibility, with no previous knowledge of the subject being assumed. Key Features: Unique in its historical coverage of citizenship in Britain - moving from the Middle Ages to the present day Reveals the great complexity of the development of citizenship in Britain Leading campaigners, politicians and theorists enliven the story and analysis Demonstrates the importance of an historical perspective in understanding the issue of citizenship in Britain today.